Peran Job Satisfaction sebagai Variabel Intervening antara Work Life Balance terhadap Employee Performance - Mei Wulandari; Hafid Kholidi Hadi (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
PDAM Giri Tirta of Gresik Regency is a Regional Owned Enterprise engaged in distributing clean water to all areas of Gresik Regency to meet the basic needs of clean water for all communities. The impact of the pandemic's environmental change has affected the work-life of employees and has an impact on the level of job satisfaction and employee performance. This study aimed to determine and explain how work-life balance affects employee performance through job satisfaction as an intervening variable. This research is a type of quantitative research. The object of the research at PDAM Giri Tirta, Gresik Regency, Menganti Branch. Sampling technique using the saturated technique, namely all populations of the research object, totalling 32 employees as the research sample. This study uses Partial Least Square (PLS) analysis with the help of SmartPLS 3.3.2 software. The results showed that work-life balance had a significant positive effect on employee performance. Work-life balance has a significant positive effect on job satisfaction. Job satisfaction has no significant effect but is positively related to employee performance, and work-life balance does not significantly affect employee performance through job satisfaction. So that job satisfaction does not have a mediating role between work-life balance and employee performance